New evidence about personality traits and risk of new complications in patients with coronary artery disease. A study by a hypnotic-derived personality classification - Roberto, Baglini; Leonardo, Baglini; Stefano, Benemeglio (Journal of Cardiovascular Medicine and Cardiology, 2020)
Five-hundred outpatients with established coronary artery disease underwent to the “analogic personality test” aiming to discriminate the bipolar subpopulation accordingly to the indication of Analogical Disciplines Italian School. Hundred-thirteen bipolar patients (Group 1) were identified and compared to the remaining three hundred-eighty seven patients during a two years clinical follow-up in order to detect possible differences in cardiac death, myocardial infarction, Cerebrovascular Accidents (CVA), re-PCI rate. Significant statistical differences were encountered for each one of the considered events but CVA while ANOVA revealed bipolar personality, diabetes, age, left ventricular ejection fraction <35% and heart failure as significant predictive variables for cardiovascular events. Bipolarism represents a new risk factor for new events in patients with established coronary artery disease.